Effect of crystalline lens decentration and tilt on visual performance in eyes implanted with bifocal or extended depth of focus intraocular lenses - Yu Zhang; Jiaqing Zhang; Chen Liang; Yifan Xu; Jiaying Wu; Junming Wu; Yifan Zhang; Aixia Jin; Xuhua Tan; Lixia Luo (BMC Ophthalmology)
Abstract Purpose To explore the potential of crystalline lens decentration and tilt as indicators for screening cataract patients for presbyopia-correcting intraocular lens (IOL) implantation. Methods Prospective observational study. Patients undergoing phacoemulsification with bifocal (Tecnis ZMB00) or extended depth-of-focus (EDOF) (Tecnis ZXR00) IOL implantation were consecutively enrolled. The decentration and tilt of the crystalline lens and the IOL were quantified through the utilization of swept-source optical coherence tomography (SS-OCT, Casia2). Postoperative visual acuity (VA), contrast sensitivity (CS), objective optical quality, and patient-reported outcomes were assessed at a 3-month follow-up. A LOWESS (LOcally WEighted Scatterplot Smoothing) curve was employed to analyze the changes in VA, CS, and objective optical quality relative to the decentration or tilt of crystalline lenses. A further comparison of visual outcomes was conducted based on the inflection points suggested by the curves. Results Eighty‑seven patients with ZMB00 IOL and 76 patients with ZXR00 IOL were included. Multiple 6-mm internal aberrations showed a nonlinear increase with greater crystalline lens decentration. The inflection points for the steep increase were observed to be 0.28 mm for the bifocal group and 0.35 mm for the EDOF group. Beyond these points, internal aberrations such as coma increased significantly (all P < 0.01). Patient satisfaction decreased (P < 0.01). Moreover, the bifocal group exhibited a decline in spectacle-independence from 98.67% to 83.33% (P = 0.049), along with a reduction in CS (P < 0.05). Conclusions The increased decentration of crystalline lenses compromises specific visual quality aspects in eyes implanted with ZMB00 and ZXR00 IOLs, with cut-off values of 0.28 mm and 0.35 mm, respectively.